Fixation of the Cartilaginous Vault with Barbed Suture in Closed-Approach High-Septal-Resection Dorsal Preservation Rhinoplasty - Erdal, Ayhan I.; Genç, İbrahim G.; Manav, Safa; Tatar, Sedat (Facial Plastic Surgery, 2022)
Fixation of the cartilaginous vault is an important maneuver in preservation rhinoplasty to reduce hump recurrences. This paper presents a cartilaginous vault fixation technique with a barbed suture. Forty-six patients who underwent closed-approach high-septal-resection dorsal preservation rhinoplasty between August 2019 and March 2020 were included in this retrospective study. According to the cartilaginous vault fixation sutures applied, the patients were divided into two main groups as follows: (1) barbed suture and (2) conventional suture. Standardized postoperative 1-month lateral view photographs were scanned for the presence of any degree of hump recurrence. The Rhinoplasty Outcome Evaluation (ROE) scale was applied at 12 months. Hump recurrence was detected in one patient in the barbed suture group (n = 21) and one patient in the conventional suture group (n = 25; p > 0.05). For the ROE scores and number of satisfied patients, no statistically significant difference was found between the barbed and conventional suture fixation techniques (p > 0.05). Fixation with barbed suture showed similar results to conventional suture fixation. Barbed sutures can be used for cartilaginous vault fixation, taking advantage of the ease of placement in closed rhinoplasty. This study reflects level of evidence IV.
Keywords: dorsal preservation rhinoplasty; barbed suture; patient satisfaction